Professor Harvey Goldstein at 80. Issue 1 (29th January 2020) - Harron, Katie; Leckie, George; Browne, Bill; Carpenter, James; Steele, Fiona; Cole, Tim
Abstract: Goldstein's Otto Wolff Lecture was delivered on 30 October 2019, on the date of his 80th birthday. Earlier that day, his colleagues Katie Harron, George Leckie, Bill Browne, James Carpenter and Fiona Steele gave talks about their work with him. Here, Tim Cole joins them to offer a brief retrospective on Goldstein's career